Prevalence of antibiotic resistance genes in the oral cavity and mobile genetic elements that disseminate antimicrobial resistance: A systematic review. (17th June 2022) - Brooks, Laura; Narvekar, Unnati; McDonald, Ailbhe; Mullany, Peter
Abstract: The objective of this review was to assess the prevalence of antibiotic resistance genes in the oral cavity and identify mobile genetic elements (MGEs) important in disseminating them. Additionally, to assess if age, geographic location, oral site, bacterial strains and oral disease influence the prevalence of these genes. Three electronic databases (Medline, Embase and the Cochrane Library) were used to search the literature. Journals and the grey literature were also hand searched. English language studies from January 2000 to November 2020 were selected. Primary screening was performed on the titles and abstracts of 1509 articles generated. One hundred and forty‐seven full texts were obtained to conduct the second screening with strict inclusion and exclusion criteria. Forty‐four final articles agreed with the inclusion criteria. Half of the studies were classed as low quality. tet (M) was the most prevalent gene overall and the conjugative transposon Tn 916 the most common MGE associated with antibiotic resistance genes in the oral cavity. In babies delivered vaginally, tet(M) was more prevalent, whilst tet(Q) was more prevalent in those delivered by C‐section. Generally, countries with higher consumption of antibiotics had higher numbers of antibiotic resistance genes. Agricultural as well as medical use of antibiotics in a country should always be considered. Between healthy, periodontitis and peri‐implantitis subjects, there was no difference in the prevalence of tet (M); however, erm (B), tet (M) and tet (O) were higher in carious active children than the non‐carious group. Subjects with poor oral hygiene have more pathogenic bacteria that carry resistance genes compared to those with good oral hygiene. Enterococcus faecalis isolates demonstrated significant tetracycline resistance ( tet (M) up to 60% prevalence in samples) and erythromycin resistance ( erm (B) up to 61.9% prevalence in samples), periodontal pathogens showed significant beta‐lactam resistance with bla Z and cfx A present in up to 90%–97% of samples and the normal oral flora had a high level of erythromycin resistance with mef (A/E) present in 65% of Streptococcus salivarius isolates. The most common resistance gene was tet (M) in root canals, cfx A in subgingival plaque, erm (B) in supragingival plaque and tet (W) in 100% of whole saliva samples. The review highlights that although many studies in this area have been performed, 50% were classed as low quality. We advise the following recommendations to allow firm conclusions to be drawn from future work: the use of large sample sizes, investigate a broad range of antibiotic resistance genes, improved methodologies and reporting to improve the quality of genetic testing in microbiology and randomisation of subject selection.